The association of lymph node involvement with lenfovascular invasion, perineural invasion and peritumoral lymphocytic reaction in surgically treated colon cancer patients (Annals of Medical Research, 2021)
Aim: The American Joint Committee on Cancer (AJCC) tumor-node-metastasis (TNM) cancer staging system is the strongest prognostic parameter for colorectal cancer. However, additional markers are needed to improve clinical decision making. The aim of this study was to investigate the effects of lenfovascular invasion (LVI), perineural invasion (PNI) and peritumoral lymphocytic reaction (PLR) on lymph node involvement in surgically treated colon cancer patients.Materials and Methods: The historical records of patients having undergone colon cancer surgery in the Department of General Surgery were evaluated. In addition to demographic data and pathological TNM staging, parameters including tumor location, type, differentiation, LVI, PNI, PLR and tumor growth pattern were recorded and analyzed. p